2019
DOI: 10.1097/sla.0000000000002450
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Effect of RAS and Evolutionary High-risk TP53 Double Mutation in Colorectal Liver Metastases

Abstract: Concomitant RAS and TP53 mutations are associated with decreased survival after CLM resection. A high EAp53 predicts a subset of patients with worse prognosis. These preliminary analyses suggest that surgical resection of liver metastases should be carefully considered in this subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(107 citation statements)
references
References 32 publications
7
100
0
Order By: Relevance
“…This meta‐analysis did not report on the pooled median OS to allow comparisons with unresectable CRLM patients. However, individual studies have reported median OS for KRAS vs wild‐type tumors as 42 vs 63.3 months, 44.9 vs 59.8 months, and 48 vs 71 months, respectively …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This meta‐analysis did not report on the pooled median OS to allow comparisons with unresectable CRLM patients. However, individual studies have reported median OS for KRAS vs wild‐type tumors as 42 vs 63.3 months, 44.9 vs 59.8 months, and 48 vs 71 months, respectively …”
Section: Resultsmentioning
confidence: 99%
“…In addition to different KRAS variants, the effects of genetic cooperation of other mutations concomitant to the RAS mutations was only recently investigated. Chun et al found that the survival of patients with concurrent RAS and high EAp53 mutations was as low as 12.2%, raising the question of whether those patients would benefit from surgery. The broader message of this study is that the interplay of concurrent mutations should be considered.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In addition, co-occurrence of RAS and TP53 mutations is associated with shorter overall survival (OS). 5 The presence of BRAF mutation is also a poor prognostic marker associated with higher risk of recurrence. [6][7][8] While some patients with limited CLM can be cured, many CRC patients have liver metastases too extensive for resection or recur after surgery.…”
Section: Introductionmentioning
confidence: 99%